Rehabilitasi Tanah Bekas Tambang Emas Dengan Pemberian Fungi Mikoriza Arbuskular (FMA) Terhadap Pertumbuhan Bibit Tanaman Naga Di Kabupaten Sijunjung - Yummama Karmaita; Taufiq Hidayat (Faculty of Agriculture, Universitas Malikussaleh, 2019)
The purpose of this research is to see growth and get the best dose of the growth of dragon seeds in the land of the former gold mine. This study used a Completely Randomized Design (CRD) 3 levels of treatment and was repeated 3 times so that 9 experimental units were obtained. The treatments used were A0 (0 g / plant), A1 (20 g / plant), and A2 (25 g / plant). The research data were analyzed using the ANOVA table at the 5% significance level if the F count is greater than the F% table 5%, then a further test of Honestly Significant Difference (BNJ) was at the 5% real level. The observed variables were the time of emergence of shoots, when the bud appears, length of shoots, and the percentage of seedlings that lived and the correlation between observed variables. The results of this study are that in general dragon plant seedlings have been able to grow well on former gold mine soil. Of the three treatments given a dose of 0 g / polybag was the best dose of the time the bud appeared (31.00 days after planting) and the number of tillers (3.00 stems) formed. The dose of 25 g / polybag is the best dose of shoot length (33.22 cm).